PEMANFAATAN TEKNOLOGI INFORMASI UNTUK DESAIN KEMASAN DAN LABEL SARUNG GEBENG DESA LIMBANG JAYA - Amran, Ali; Desiani, Anita; Primartha, Rifkie; Suprihatin, Bambang; Ermatita, Ermatita; Salamah, Fitri (LPPM Universitas Nusa Mandiri, 2025)
Gebeng Sarong is a typical woven fabric from Limbang Jaya village, Ogan Ilir Regency, South Sumatra. This craft is increasingly disappearing due to the difficulty of marketing carried out by Limbang Jaya village craftsmen. The packaging and brands used on Gebeng Sarongs are still very simple and unattractive so their marketing is less able to compete with similar products. The lack of creativity of craftsmen in Limbang Jaya is also due to the low level of education of the craftsmen, only elementary or junior high school graduates. In addition, the location of the village is rather remote, causing Gebeng Sarongs to have limited marketing. To help overcome this problem, the Sriwijaya University team held a training activity for craftsmen to develop their products for a wider market with attractive packaging. The stages of this activity include: problem identification, activity preparation, activity implementation, and activity evaluation. The activities carried out were in the form of training activities for craftsmen on the use of information technology and graphic applications., Training activity materials included an introduction to the Canva application, tutorials on making packaging and packaging designs, and direct practice. Based on the results of the pre-test and post-test it can be concluded that this activity has succeeded in improving the skills of craftsmen in designing aesthetic packaging according to market needs, thereby increasing the appeal of Gebeng Sarong in a wider market. This activity is also expected to help maintain the Gebeng Sarong as the typical fabric of the South Sumatra.